Bioactive compounds from Hypericum humifusum and Hypericum perfoliatum: inhibition potential of polyphenols with acetylcholinesterase and key enzymes linked to type-2 diabetes - Afef Béjaoui; Issam Ben Salem; Nesrine Rokbeni; Yassine M’rabet; Mohamed Boussaid; Abdennacer Boulila (Pharmaceutical Biology, 2017)
Context: Natural products are reported to have a wide spectrum of pharmacological properties such as antimicrobial, anti-inflammatory and anti-cholinesterase. The genus Hypericum (Hypericaceae) is a source of a variety of molecules with different biological activities, notably hypericin and various phenolics. Objectives: The goals of the present work were the determination of total phenolic and flavonoid content, hypericin and hyperforin concentration as well as the evaluation of biological of Hypericum humifusum L. (Hhu) and Hypericum perfoliatum L. (Hper). Materials and methods: The various extracts of aerial parts were powdered, and then extracted with methanol. Antibacterial activity was performed according to minimum inhibitory concentration (MIC) and minimum bactericidal (MBC) methods against four Gram-positive bacteria, four Gram-negative bacteria and yeast. Results: The results revealed that H. humifusum, bear the highest total phenolic and flavonoid content (48–113 mg GAE/g and 8–41 mg RE/g, respectively) as well as hypericin (60–90 mg/g) and hyperforin (8–30 mg/g) concentration. Both species showed significant antioxidant activity as revealed by DPPH, FRAP, ABTS, and metal chelating assays. H. humifusum exhibited a strong acetylcholinesterase (3.86–4.57 mg GALAEs/g), α-glucosidase (0.73–2.55 mmol ACEs/g) and α-amylase (3–8 mmol ACEs/g) inhibitory activity. The extract of H. humifusum exhibited strong antibacterial activity mainly against Staphylococcus epidermidis, Staphylococus aureus, and Enterococcus faecium (MIC values ranging from 200 to 250 μg/mL). The highest antifungal activity was showed for H. perfoliatum extract (MIC value = 250 μg/mL). Conclusion: The data suggest that H. humifusum could be used as valuable new natural agents with functional properties for pharmacology industries.